2012
DOI: 10.1590/s0100-40422012000800022
|View full text |Cite
|
Sign up to set email alerts
|

Composição química de aguardentes de cana-de-açúcar fermentadas por diferentes cepas de levedura Saccharomyces cerevisiae

Abstract: Recebido em 16/2/12; aceito em 11/4/12; publicado na web em 20/7/2012 CHEMICAL COMPOSITION OF SUGAR CANE SPIRITS FERMENTED BY DIFFERENT Saccharomyces cerevisiae YEAST STRAINS. The aim of this study was to evaluate the chemical composition of sugar cane spirits, fermented by different commercial Saccharomyces cerevisiae yeast strains and double distilled by pot still. Sugar cane juices were separately fermented by yeasts CA-11, Y-904, BG-1, PE-2, SA-1 and CAT-1 and distilled by pot still according to the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
0
14
0
8
Order By: Relevance
“…Oliveira (2010), while preparing a cagaita fermented alcoholic beverage using CA-11 yeast, observed a total acidity content of 55.59 meq L -1 , which is also within the limits specified by law (Brasil, 2012). Alcarde et al (2012), after comparing the chemical composition of sugarcane spirits fermented by different S. cerevisiae commercial strains, concluded that spirits obtained through fermentations with CA-11, BG-1, and CAT-1 yeasts showed chemical composition within the limits established under Brazilian law. In addition, they also found that the CA-11 strain was the one that produced spirits with the best chemical composition related to sensory quality.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira (2010), while preparing a cagaita fermented alcoholic beverage using CA-11 yeast, observed a total acidity content of 55.59 meq L -1 , which is also within the limits specified by law (Brasil, 2012). Alcarde et al (2012), after comparing the chemical composition of sugarcane spirits fermented by different S. cerevisiae commercial strains, concluded that spirits obtained through fermentations with CA-11, BG-1, and CAT-1 yeasts showed chemical composition within the limits established under Brazilian law. In addition, they also found that the CA-11 strain was the one that produced spirits with the best chemical composition related to sensory quality.…”
Section: Resultsmentioning
confidence: 99%
“…One of the yeast strains selected for cachaça production is CA-11. Alcarde et al (2012) found that strain CA-11 provided the most appropriate chemical composition to the distillate compared with the other strains studied (Y-904, BG-1, PE-2, SA-1 and CAT-1). Action of CA-11 is different from other strains during fermentation.…”
Section: Introductionmentioning
confidence: 81%
“…Accordingly, the concentration of acetic acid, succinic acid, glycolic acid, citramalic acid and lactic acid was much higher in the last fraction, whereas capric acid, lauric acid, myristic acid, and palmitic acid were more abundant in the initial fractions (Serafim et al, 2011). Alcarde et al (2012) studied the yeast strain CA-11 in double distilled cachaça and found that volatile acidity in the first, heart and last fractions was 14.20, 23.67 and 124.51 mg 100 mL -1 , respectively, indicating that the volatile acid content was higher in the last fraction.…”
Section: Filtration Of All Replicates Using a Single Charcoal Columnmentioning
confidence: 94%
See 2 more Smart Citations